2020
DOI: 10.3390/ijms22010210
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Rat Accumbens Dopamine, Endocannabinoids and GABA Content During WIN55,212-2 Treatment: The Role of Ghrelin

Abstract: The endocannabinoid/CB1R system as well as the central ghrelin signalling with its growth hormone secretagogoue receptors (GHS-R1A) are importantly involved in food intake and reward/reinforcement processing and show distinct overlaps in distribution within the relevant brain regions including the hypothalamus (food intake), the ventral tegmental area (VTA) and the nucleus accumbens (NAC) (reward/reinforcement). The significant mutual interaction between these systems in food intake has been documented; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…THC-CPP development was also reduced after the simultaneous administration of JMV2959 and THC during conditioning. JMV2959 also significantly reduced THC-induced behavioral stimulation in the LABORAS cage [ 215 ], similarly to a later experiment involving the synthetic aminoalkylindol cannabinoid WIN55,212-2-induced behavioral stimulation [ 216 ]. Furthermore, JMV2959 pretreatment significantly attenuated the WIN55,212-2 intravenous self-administration (IVSA) in rats [ 215 ].…”
Section: Ghrelin/ghs-r1as and Cannabinoidsmentioning
confidence: 91%
See 3 more Smart Citations
“…THC-CPP development was also reduced after the simultaneous administration of JMV2959 and THC during conditioning. JMV2959 also significantly reduced THC-induced behavioral stimulation in the LABORAS cage [ 215 ], similarly to a later experiment involving the synthetic aminoalkylindol cannabinoid WIN55,212-2-induced behavioral stimulation [ 216 ]. Furthermore, JMV2959 pretreatment significantly attenuated the WIN55,212-2 intravenous self-administration (IVSA) in rats [ 215 ].…”
Section: Ghrelin/ghs-r1as and Cannabinoidsmentioning
confidence: 91%
“…Recent microdialysis study in rats [ 216 ] found that the administration of WIN55,212-2 into the posterior VTA induced significant dopamine release in the NAC shell, which was significantly reduced by systemic JMV2959 pretreatment. Simultaneously, the cannabinoid-increased accumbens dopamine metabolic turnover was significantly augmented by JMV2959 pretreament, with the monoamine oxidase (MAO) metabolism products and their turnover being the most increased (DOPAC/dopamine, HVA/dopamine).…”
Section: Ghrelin/ghs-r1as and Cannabinoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, JMV2959 reduces morphine-induced locomotor stimulation and stereotypic behavior in male rodents (Sustkova-Fiserova et al, 2014 ). Additionally, JMV2959 have been shown to inhibit elevated accumbal dopamine levels and CPP caused by cannabinoids in male rats (Charalambous et al, 2020 , 2021 ). Regarding chronic use and SUD, plasma ghrelin has been associated with cocaine-seeking and expectancy (Tessari et al, 2007 ; You et al, 2019 ), whereas systemic administration of JMV2959 reduces self-administration of methamphetamine in rats (Havlickova et al, 2018 ).…”
Section: Appetite-regulatory Peptides In Substance Use Disordermentioning
confidence: 99%